Public relations strategies in religious organizations: a qualitative study of Muhammadiyah’s organizational communication - Sumarlan, Iman; Muktiyo, Widodo; Pawito, Pawito; Rahmanto, Andre Noevi (Frontiers in Communication, 2025)
Muhammadiyah, one of Indonesia’s most influential Islamic organizations, is crucial in shaping the country’s socio-religious landscape through Islam Berkemajuan (Progressive Islam). To sustain its identity and legitimacy, Muhammadiyah implements structured public relations (PR) strategies that engage stakeholders and reinforce its ideological position. Beyond promotion, PR in religious organizations is a tool for institutional sustainability, stakeholder relations, and public perception management. This study examines Muhammadiyah’s PR strategies using the Communicative Constitution of Organizations (CCO) theory and the Cultural Approach to Organizational Communication. A qualitative approach is employed, integrating semi-structured interviews and document analysis to explore communication’s role in shaping organizational identity. McPhee’s Four Flows model analyzes membership negotiation, self-structuring, activity coordination, and institutional positioning, while the Cultural Approach explains how Muhammadiyah embeds its values into symbols, narratives, and rituals. Findings indicate that Muhammadiyah reinforces its identity through structured messaging, internal cohesion, and digital adaptation. By balancing religious authenticity with modern communication tools, the organization maintains relevance in a dynamic society. The study expands the application of CCO theory in religious organizations and provides practical insights for faith-based institutions. Future research should examine the impact of digital communication on younger audiences and compare PR strategies across religious organizations.